2002
DOI: 10.1046/j.0007-1331.2001.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Corticotropin‐Releasing Factor Receptor Expression and Adrenocorticotropic Hormone Responsiveness in Anterior Pituitary Cells of Wistar‐Kyoto Rats

Abstract: The Wistar-Kyoto (WKY) rat shows signs of persistent activation of the hypothalamic-pituitary-adrenal axis, but the cause and site of this activation is not yet known. Chronically activated corticotrophs generally show blunted adrenocorticotropic hormone (ACTH) response to corticotropin releasing factor (CRF); therefore, the anterior pituitary responsiveness to ACTH secretagogues, CRF and vasopressin, was compared in male WKY and Wistar rats. Anterior pituitary CRF binding and CRF receptor mRNA expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Animal models utilizing invasive techniques that can rarely be implemented in human subjects are often used in this confirmatory manner. For example, a recent rodent study confirmed the hypothesis that diminished CRF receptor binding in the anterior pituitary is associated with a blunted ACTH response to CRF stimulation (Hauger et al, 2002). Preclinical data is certainly informative; however, its utility is limited by the incomplete homology of any animal model for the human condition (Newport et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models utilizing invasive techniques that can rarely be implemented in human subjects are often used in this confirmatory manner. For example, a recent rodent study confirmed the hypothesis that diminished CRF receptor binding in the anterior pituitary is associated with a blunted ACTH response to CRF stimulation (Hauger et al, 2002). Preclinical data is certainly informative; however, its utility is limited by the incomplete homology of any animal model for the human condition (Newport et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated or prolonged stimulation with CRH reduces CRH receptor binding and can cause reduced ACTH responsiveness or desensitization [31]. Indeed chronically activated corticotrophs generally show blunted ACTH response to CRH [32]. To test the hypothesis that IS exposure decreases the responsiveness of the anterior pituitary to CRH, quartered anterior pituitaries were assessed for their ability to release ACTH in response to in vitro CRH stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…A blunted ACTH response to CRH has consistently been found in adult patients with severe melancholic major depressive ill-ness~Gold, Holsboer et al, 1984!. The ACTH response may be blunted because of downregulation of pituitary CRH receptors in response to chronically increased hypothalamic CRH secretioñ Hauger et al, 2002;Newport et al, 2003! and0or loss of fast-feedback regulation in the hypothalamus and hippocampus~Young, Haskett, Murphy-Weinberg, Watson, & Akil, 1991!. A normal cortisol response to blunted ACTH secretion is evidence of a hyperresponsive adrenal cortex, reflecting a disruption in the homeostasis of the HPA axis~Gold et al, 1995!. Because these children were not hypercortisolemic at baseline, it is likely that they are in a state of relatively mild hypersecretion of hypothalamic CRH.…”
Section: Offspring Diagnosismentioning
confidence: 99%